Hubungan Regulasi Diri Dengan Kecanduan Game Online Siswa MAN di Kota Bukittinggi - Adzkia, Naufal; Nurfarhanah; Sukmawati, Indah; Zola, Nilma; Febriani, Rahmi Dwi (Mataram University, 2025)
This study aims to examine the relationship between self-regulation and online game addiction among students of MAN in Bukittinggi City. The increasing intensity of online gaming among adolescents has raised concerns regarding their academic achievement and social behavior. This research employed a quantitative approach with a descriptive correlational method. The participants were 11th-grade students selected through purposive sampling. The instruments used included a self-regulation scale based on Zimmerman’s theory (2000) and an online game addiction scale based on Young’s theory (2010). Data analysis using a simple linear correlation test revealed a positive and significant relationship between self-regulation and online game addiction (r = 0.292; p = 0.026). The coefficient of determination of 8.5% indicates that self-regulation contributes minimally to online game addiction. These findings suggest that students with higher self-regulation are better able to manage their gaming time, whereas those with lower self-regulation tend to be more addictive. This study is expected to serve as a reference for schools and parents in fostering students’ self-regulation skills through guidance and digital literacy initiatives.